2017
DOI: 10.1002/term.2360
|View full text |Cite
|
Sign up to set email alerts
|

Human corneal fibroblast migration and extracellular matrix synthesis during stromal repair: Role played by platelet‐derived growth factor‐BB, basic fibroblast growth factor, and transforming growth factor‐β1

Abstract: The development of treatments that modulate corneal wound healing to avoid fibrosis during tissue repair is important for the restoration of corneal transparency after an injury. To date, few studies have studied the influence of growth factors (GFs) on human corneal fibroblast (HCF) expression of extracellular matrix (ECM) proteins such as collagen types I and III, proteoglycans such as perlecan, or proteins implicated in cellular migration such as α5β1-integrin and syndecan-4. Using in vitro HCFs, a mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…We observed a significant up-regulation of collagen type I and III mRNA expression levels in the wound area. This was consistent with previous in vitro studies that also found an up-regulation of collagens type I and III by cultured human myofibroblasts and cultured bovine myofibroblasts (Funderburgh et al, 2001;Gallego-Munoz et al, 2018). The presence of both collagen types has been described during corneal scarring by Massoudi et al (2016), indicating the presence of a disorganized ECM that was related to the loss of transparency, as we found here.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed a significant up-regulation of collagen type I and III mRNA expression levels in the wound area. This was consistent with previous in vitro studies that also found an up-regulation of collagens type I and III by cultured human myofibroblasts and cultured bovine myofibroblasts (Funderburgh et al, 2001;Gallego-Munoz et al, 2018). The presence of both collagen types has been described during corneal scarring by Massoudi et al (2016), indicating the presence of a disorganized ECM that was related to the loss of transparency, as we found here.…”
Section: Discussionsupporting
confidence: 93%
“…During wound healing, the quiescent keratocytes present in the stroma are activated and transitioned into the repair phenotypes fibroblasts and myofibroblasts that synthesize and release ECM components in the wound area. Myofibroblasts proliferate and migrate towards the site of the injury to close the wound by depositing excessive amounts of ECM proteins, including collagens type I, III, IV, and V to facilitate tissue repair (Chaurasia et al, 2015;Gallego-Munoz et al, 2018;Tandon et al, 2010). During this process, the collagen type I/type III ratio can be disrupted, and this fact has been described as one of the main reasons for corneal opacity after corneal injury (Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that ECM composition can modulate corneal behavior in 3-D culture in response to PDGF BB, which stimulates corneal fibroblast spreading and migration [ 28 , 29 , 30 , 31 , 32 ]. Specifically, whereas corneal fibroblasts generally move independently within 3-D collagen matrices, fibrin induces a switch to an interconnected, collective mode of cell spreading and migration that is independent of differences in ECM stiffness [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that PDGF-BB and bFGF are involved in corneal wound healing, but their actions on ECM synthesis were not well understood [52, 53]. After scratch wound injury, PDGF-BB and bFGF-treated HCF wound had a similar healing pattern, and the wounds were completely closed at day 10, while wound in serum-free media had a slower healing rate [54]. In the same study, PDGF-BB-treated cells also had a higher level of collagen III expression, which is a marker of repair matrix synthesis.…”
Section: Resultsmentioning
confidence: 99%